Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Preferensi Nasabah Menabung di BTN Syariah Jambi - Akbar, Akhmad; Kurniawan, Bambang; Ayahrizal, Ahmad (Ebisma (Economics, Business, Management, & Accounting Journal), 2025)
This study aims to examine the effect of product quality and service quality on customer preferences at Bank BTN Syariah Jambi. This research employs a quantitative descriptive approach. The type of research is quantitative descriptive. Data were obtained through questionnaires, observations, and documentation. The method used to analyze the data is multiple regression analysis. The sample was selected using purposive sampling, with a total of 90 customers. The results indicate that both product quality and service quality have a partial and simultaneous effect on saving preferences at BTN Syariah Jambi. Simultaneously, there is a positive influence between product quality and service quality variables on customers' saving preferences, with the F-test result showing a significance value of 0.000 < 0.05. The product quality variable obtained a t-test significance value of 0.000 < 0.05, and the service quality variable obtained a t-test significance value of 0.011 < 0.05